Marriage, perversion & power : the construction of moral discourse in Southern Rhodesia (Zimbabwe), 1890-1930 - Jeater, D (1990)
The power of the rural patriarchs in the region which became known as Southern Rhodesia depended, in the 1890s, upon their control over marriage alliances. Meanwhile, in Europe, the power to control sexual behaviour was becoming linked to the distinction between 'moral' matters which were no concern of the State, and 'perverse' matters, subject to legislative control. The occupying administration established in 1890, spurred by internal political disputes, deemed African male sexuality to be 'perverse', using this to justify its attempts to undermine rural patriarchs and proletarianise African women. Simultaneously, the whites introduced new social environments, where lineage links were not the primary determinant of people's interactions with one another, and encouraged large numbers of single men from across the sub-continent into Southern Rhodesia, to work there. These changes inevitably affected the ways in which members of the African communities perceived themselves. Individualist notions of sexual choice were encouraged by BSACo legislation, while the spread of migrant labour created situations in which men and women could actually make such choices. Rural patriarchs lobbied for State support in their attempts to control women and their seducers. This support came in 1916 with the Natives Adultery Punishment Ordinance, which, although ostensibly supporting 'traditional' patriarchal power, actually reinforced the notion that individuals, and women in particular, were alone answerable for their sexual choices. Meanwhile, fears about African male 'perversity' in the white communities combined with the appearance of African prostitution to challenge African ides about what was valuable in 'men' and 'women' and to suggest that sexuality was something that could be used and abused outside any wider implications regarding lineage obligation. Africans began to accept the notion of 'immorality' as applied to independent women. By the 1930s, the internal politics of the white community saw this typification extended to all African women, alongside the fear of African men as 'perverse'.